2007
DOI: 10.1182/asheducation-2007.1.420
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Elderly Patients with AML and the Implications for Treatment

Abstract: The outcome of older patients with acute myeloid leukemia (AML) has not improved in the last three decades. These patients are more likely to have comorbid illness, poor performance status, and impaired organ function. These clinical features limit their ability to tolerate intensive cytotoxic chemotherapy and result in greater early mortality. The AML seen in elderly patients is also more likely to have evolved from a prior hematologic disorder, and the leukemic blasts are more likely to have poor-risk struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 57 publications
3
31
1
8
Order By: Relevance
“…However, as expected, blast phase patients with loss of chromosomal material on 7q showed poor survival, because this is known to be predictive for rapid progression and poor response in AML therapy. [35][36][37] MPN-blast phase patients with cytogenetically undetectable 7qCNN-LOH had comparable survival rates to those with Ϫ7/7qϪ in their leukemic cells, which is in accordance with previously published data. 44 In addition, 9pCNN-LOH with homozygous JAK2 mutation was also linked to an inferior outcome in MPN-blast crisis in comparison with patients with either heterozygous JAK2V617F or wild-type JAK2.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, as expected, blast phase patients with loss of chromosomal material on 7q showed poor survival, because this is known to be predictive for rapid progression and poor response in AML therapy. [35][36][37] MPN-blast phase patients with cytogenetically undetectable 7qCNN-LOH had comparable survival rates to those with Ϫ7/7qϪ in their leukemic cells, which is in accordance with previously published data. 44 In addition, 9pCNN-LOH with homozygous JAK2 mutation was also linked to an inferior outcome in MPN-blast crisis in comparison with patients with either heterozygous JAK2V617F or wild-type JAK2.…”
Section: Discussionsupporting
confidence: 81%
“…Abnormalities involving chromosome 7 are frequently detectable in de novo and secondary AML, [34][35][36][37] and preceding studies have found a critical breakpoint region involving a locus at centromeric band 7q22, whereas the telomeric breakpoint varies from q32 to q36. Interestingly, the minimal deleted region in our cohort was located at 7q22.1 encompassing only 2 promising target genes, SH2B2 (previously named APS) and CUTL1.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased MDR gene expression (MDR1 and ABCG2) was associated with poorer overall survival (OS) rates in a gene expression profiling study among adults with acute myeloid leukemia (AML) (Wilson et al, 2006). Elevated P-gp expression was identified more frequently among older versus younger patients with AML (Erba, 2007), which reflects the greater resistance to therapy and the poorer prognosis seen for older patients with AML. Because of the importance of MDR gene expression, the contributions of genetic polymorphisms to intrinsic MDR have been investigated extensively, to determine whether specific genotypes or haplotypes are associated with responses to therapy (Leschziner et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of older patients with AML has not improved in the last three decades (Erba, 2007). This likely reflects a worse biology in older patients with AML in addition to decreased tolerability of treatment.…”
Section: Discussionmentioning
confidence: 99%